Optimum Operating Parameters for Hollow Fiber Membranes in Direct Contact Membrane Distillation - Rashid, Khalid T.; Sunarti, Abd Rahman; Alsalhy, Qusay (Springer, 2016)
The aim of this study is the optimization of the operating conditions of PVDF-co-HFP hollow fiber membrane for direct contact membrane distillation applications. The influence of the operation parameters, such as the feed temperature (40–80 \({^{°} C}\)), the feed flow rate (0.3–0.6L/min), and the PVP content (0–9%), as well as the feed concentration increased from 3.5 to 5.0 wt%, and their interactions on the PVDF-co-HFP hollow fiber membrane permeate flux have been investigated. The optimum operating parameters have been specified using second-order FULL FACTORIAL and Taguchi optimization techniques to find optimum values for operation parameters in the DCMD process in order to obtain a good value of permeate flux. The results showed that PVDF-co-HFP membrane has the best performance at 21 (\({{kg/m}^{2} \,{h}}\)) when a hot feed temperature of 80\({^{°} C}\) with 0.6 L/min flow rate, 3.5wt% NaCl feed concentration and 9 wt% PVP content in the casting solution were used. The PVP % content and inlet temperature had a significant impact on the permeate flux, while feed flow rate and feed concentration have less influence.